Perception and preference of umami-taste-containing foods based on olfaction and (or) gustation - Belloute, Rachida; Diouri, Mohammed (Recent Research in Science and Technology, 2016)
This study aimed at testing the ability to perceive and identify smells and tastes and determining the role of olfaction in the perception and preference of foods containing umami taste in both sexes. It covered a sample of 28 naive subjects aged 12-65 years, men and women, chosen at random, belonging mainly to the city of Meknes (Morocco). Our study consisted of three experimental tests: One test of smelling and two tests of tasting, with or without a disturbing odor. The tests were carried out according to the IMANOR standard ISO 6658: 2007. Qadid (air-dried salted meat) was similar to plain meat with respect to perception and preference. This food would not be able to represent the umami taste. The presence of a strong lemon smell reduced cheese identification by gustation. This food would contribute to flavor more by its taste than by its smell. Women were more effective in detecting onion by gustation as well as by olfaction; whereas men were more efficient in detecting cheese by both routes. However, it seems that the impact of olfaction on choice is not gender dependent.